(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Work motivation is an internal force which determines employees work effectiveness. Motivation level of a teacher influence the way they participate in the education process. The present study intends to address the motivational level and organizational citizenship behaviour among rural government and private secondary school teachers. The casual comparative research design was employed and the data was obtained from 120 participants i.e. 60 government and 60 private school teachers by using work motivation questionnaire and organizational citizenship behaviour scale. The results of an independent sample t test revealed that there is no significant difference on work motivation between government and private secondary school teachers and there is a significant difference in the level of organizational citizenship behaviour in where, rural Government secondary school teachers have shown high amount of organizational citizenship behaviour than private school teachers. In further, there is no difference on the level of organizational citizenship behaviour as influenced by their level of work motivation among government secondary school teachers whereas, there is a difference among private school teachers, which indicated that teachers with higher level of work motivation have higher amount of Organizational citizenship behaviour.